THE CRITERIA FOR LYMPH NODE METASTATIC DISEASE IN UTERINE CERVIX CANCER PATIENTS BASED ON MRI FINDINGS - E. G. Zhuk; I. A. Kosenko (Сибирский онкологический журнал)
Introduction. The state of pelvic and retroperitoneal lymph nodes is an important prognostic factor for cervical cancer. Lymph node size is the most widely used CT and MR criteria for assessing lymph node status. Lymph nodes measuring more than 1cm in the short axis diameter are considered malignant. However this criterion (nodal size) is not foolproof because of a high percentage of diagnostic errors. The purpose of the study was to develop objective MRI criteria for assessing lymph node metastasis in patients with cervical cancer by measuring the short- and the long-axis diameters of lymph nodes, short axis/long axis ratio (configuration index) and to evaluate their diagnostic value. Materials and methods. The prospective study included 31 patients with histologically confirmed cervical cancer, who underwent radical surgery with standard lymph node dissection. Sixty removed lymph nodes were evaluated. MRI examinations were performed using a 1.5 T scanner in T2- weighted images (T2-WI), T1-WI and T2 weighted sequences with fatty tissue signal suppressing and diffusionweighted MRI. Results. Lymph nodes measuring ≥0.8 cm in the short axis diameter were considered suspicious for metastatic disease. The sensitivity and specificity with a cutoff of ≥0.8cm were 68 % (CI 48.3‑82.9) and 80 % (CI 63.8‑90.3), respectively; the positive and negative predictive values were 71 % and 78 %, respectively; and the accuracy was 75 % (CI 62.7‑84.3). The short axis/long axis ratio (configuration index) of <1.47 indicated a likelihood of pathology in the lymph node. The absence of the hypointense signal from the fatty hilum of lymph nodes was considered as a predictor of lymph node metastasis. The analysis of this criterion showed 80 % sensitivity (CI 60.4‑91.6), 85.7 % specificity (60.4‑91.6), 80 % PPV, 85.1 % NPV and 83.3 % accuracy (CI 60.4‑91.6). Conclusion. Lymph node size of ≥0.8 cm in the short axis diameter and the short axis/long axis ratio (configuration index) of <1.47 appeared to be significant MRI criteria in the assessment of lymph node metastasis. The additional use of MRI criterion such as the absence of the hypointense signal from the fatty hilum of the lymph node made it possible to improve diagnostic accuracy up to 92 % (CI 80.9–97.4).